Causes and Consequences of Treatment Variation in Moderate and Severe Traumatic Brain Injury: A Multicenter Study. Issue 4 (April 2017) - Cnossen, Maryse C.; Polinder, Suzanne; Andriessen, Teuntje M.; van der Naalt, Joukje; Haitsma, Iain; Horn, Janneke; Franschman, Gaby; Vos, Pieter E.; Steyerberg, Ewout W.; Lingsma, Hester
Abstract : Objectives: Although guidelines have been developed to standardize care in traumatic brain injury, between-center variation in treatment approach has been frequently reported. We examined variation in treatment for traumatic brain injury by assessing factors influencing treatment and the association between treatment and patient outcome. Design: Secondary analysis of prospectively collected data. Setting: Five level I trauma centers in the Netherlands (2008–2009). Patients: Five hundred three patients with moderate or severe traumatic brain injury (Glasgow Coma Scale, 3–13). Interventions: We examined variation in seven treatment parameters: direct transfer, involvement of mobile medical team, mechanical ventilation, intracranial pressure monitoring, vasopressors, acute neurosurgical intervention, and extracranial operation. Measurements and Main Results: Data were collected on patient characteristics, treatment, and 6-month Glasgow Outcome Scale-Extended. Multivariable logistic regression models were used to assess the extent to which treatment was determined by patient characteristics. To examine whether there were between-center differences in treatment, we used unadjusted and adjusted random effect models with the seven treatment parameters as dependent variables. The influence of treatment approach in a center (defined as aggressive and nonaggressive based on the frequency intracranial pressure monitoring) on outcome was assessed using multivariable random effect proportional odds regression models in those patients with an indication for intracranial pressure monitoring. Sensitivity analyses were performed to test alternative definitions of aggressiveness. Treatment was modestly related to patient characteristics (Nagelkerke R 2 range, 0.12–0.52) and varied widely among centers, even after case-mix correction. Outcome was more favorable in patients treated in aggressive centers than those treated in nonaggressive centers (OR, 1.73; 95% CI, 1.05–3.15). Sensitivity analyses, however, illustrated that the aggressiveness-outcome association was dependent on the definition used. Conclusions: The considerable between-center variation in treatment for patients with brain injury can only partly be explained by differences in patient characteristics. An aggressive treatment approach may imply better outcome although further confirmation is required. Abstract : Supplemental Digital Content is available in the text.